Knowledge mobilisation for chronic disease prevention: the case of the Australian Prevention Partnership Centre - Sonia Wutzke; Samantha Rowbotham; Abby Haynes; Penelope Hawe; Paul Kelly; Sally Redman; Seanna Davidson; Jackie Stephenson; Marge Overs; Andrew Wilson (BMC, 2018)
Abstract Background Cross-sectoral, multidisciplinary partnership research is considered one of the most effective means of facilitating research-informed policy and practice, particularly for addressing complex problems such as chronic disease. Successful research partnerships tend to be underpinned by a range of features that enable knowledge mobilisation (KMb), seeking to connect academic researchers with decision-makers and practitioners to improve the nature, quality and use of research. This paper contributes to the growing discourse on partnership approaches by illustrating how knowledge mobilisation strategies are operationalised within the Australian Prevention Partnership Centre (the Centre), a national collaboration of academics, policy-makers and practitioners established to develop systems approaches for the prevention of lifestyle-related chronic diseases. Methods We undertook interviews with key academics, policy, and practice partners and funding representatives at the mid-point of the Centre's initial 5-year funding cycle. We aimed to explore how the Centre is functioning in practice, to develop a conceptual model of KMb within the Centre for use in further evaluation, and to identify ways of strengthening our approach to partnership research. Inductive and deductive thematic analysis was used to identify the key mechanisms underpinning the Centre's KMb approach. Results Six key mechanisms appeared to facilitate KMb within our Centre, namely Engagement, Partnerships, Co-production, Capacity and Skills, Knowledge Integration, and Adaptive Learning and Improvement. We developed a conceptual model that articulated these mechanisms in relation to the structures and processes that support them, as well as the Centre's goals. Findings also informed adaptations designed to strengthen the Centre. Conclusions Findings provide insights into the practical realities of operationalising KMb strategies within a research partnership. Overall, the centre is perceived to be progressing towards its KMb goals, but challenges include stakeholders from different settings understanding each other's contexts and working together effectively, and ensuring knowledge generated across different projects within the Centre is integrated into a more comprehensive understanding of chronic disease prevention policy and practice. Our conceptual model is now informing ongoing developmental evaluation activities within the Centre, where it is being tested and refined.